Onset of northeast monsoon over South Peninsular India - G C, SATYANARAYANA; C V, NAIDU; D V BHASKAR , RAO; N, UMAKANTH; N, NAVEENA (MAUSAM, 2020)
The onset dates of the northeast monsoon over South Peninsular India are determined using the wind data at 850 hPa and 200 hPa, OLR, mean sea level pressure data for the domain 40° E to 120° E, 0° to 40° N. These three data sets are sourced from NCEP/NCAR reanalysis daily data sets. Further the daily grid point (0.25° Lat. × 0.25° Long.) rainfall data over India from Indian Meteorological Department is considered for delineation of rainfall pattern. The total length of the data of the above mentioned parameters is 21 years (1994 to 2014). Pentad distributions of the above parameters for the domain considered are prepared for examining the circulation patterns and rainfall activity. The pentads taken for the study are from 55th (28th September - 2nd October) pentad to 65th (17-21 November) pentad. In the determination of the northeast monsoon over South Peninsular India, the following points are considered: (i) The persistence of the northeasterlies at 850 hPa level, (ii) Occurrence of the rainfall over the South Peninsular India, (iii) Presence of east-west oriented trough [Intertropical Convergence Zone (ITCZ)] in the lower latitudes from Ethiopia region to Malaysia region passing through South Arabian Sea, southern region of South Peninsular India and South Bay of Bengal, (iv) The presence of low pressure over the southwest Bay of Bengal at the surface, (v) Persistence of a high pressure zone in northern latitudes of India (extending from the Saudi Arabia/Jordan region to the Head Bay of Bengal running through North Arabian Sea, Gujarat and Orissa), (vi) Presence of subtropical ridge at 200 hPa level around 17.5° N, (vii) Presence of north-south ridge over theeastern parts of China and (viii) Presence of relatively low OLR values over South Peninsular India when compared to the northern latitudes. If any pentad satisfies the above points, the middle date of the pentad is considered as the date of onset of northeast monsoon over South Peninsular India. If any pentad satisfies all the points except point number 2, importance is given to the persistence of northeasterlies and the middle date of the pentad will be declared as the onset date. By following the criteria, the dates of onset of northeast monsoon are determined for the latest 21 years. These dates are compared with those of the India Meteorological Department.